Pengaruh Return On Asset, Produk Domestik Bruto Dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Yang Terdaftar Di Indeks LQ45 - I Gede Agus Arya Adi Putra; I Made Pradana Adiputra (Jurnal Akuntansi Profesi, 2023)
The purpose of this research is to test whether the return on assets, gross domestic product, earnings per share affect the stock prices by testing partially. This research is a quantitative and descriptive research. The population used in this research are all companies listed on the LQ45 index with 3 years of observation, namely from 2019-2021. The amount of population in this research are 45 companies and samples that fulfill the criteria according to purposive sampling are 29 companies. The data analysis technique used is multiple linear regression analysis. The results of the analysis showed that, (1) return on assets have no effect of stock prices in companies listed on the LQ45 index, (2) gross domestic product have no effect on stock prices in companies listed on the LQ45 index, (3) earnings per share have a significant effect on stock prices in companies listed on the LQ45 index Keywords : Return On Assets, Gross Domestic Product, Earnings Per Share, Stock Prices